'The cruelty of righteous people': Niebuhr on the urgency of cruelty. (June 2021) - Steele, Brent J
This paper responds to critics of Reinhold Niebuhr by exploring two themes important for locating his views on cruelty's emergence in modern society. The first relates to his basic insight into the relationship between individual morality and group loyalty and solidarity. Niebuhr provides a sophisticated argument for such group dynamics in his work, issued in Moral Man, Immoral Society, as well as his essays on race. These also form the basis for his second thematic argument regarding cruelty, the role of 'righteousness' as it relates to security and insecurity. Niebuhr's views on race, I argue, need to be considered more broadly as an example of his views on groups, power, and cruelty. The paper concludes with some modest proposals for thinking about combatting cruelty via Niebuhr's counsel.